Digitalization as a Tool for the Speech Development of Older Preschool Children with Autistic Disorders - Bogush, A.; Palahnyuk, Olha (My University, 2024)
Autism is a neurological condition characterized by long-term and serious difficulties in communication and social interaction, so innovative methods are being sought worldwide to influence language development in such children. The study aims to study the influence of digitalization on the development of speech of senior preschool children with autistic disorders. Research methods: we examined 68 children of senior preschool age with autistic disorders (5 to 7 years old), of whom 38 were girls (55.9%) and 30 boys (44.1%). The child’s speech development was carried out using specialized mobile software applications for 6 months for 1.5 hours a day. Results: the use of mobile software applications did not lead to the improvement of receptive speech in children with autistic disorders. In contrast, the percentage of children with expressive speech decreased: 19 (27.9%) vs 23 (33.8%), speech deficit - 28 (41.2%) vs. 35 (51.5%); the percentage of children with communicative speech increased - 39 (57.4%) vs. 30 (44.1%). Conclusions. It has been established that it is necessary to apply digitalization in speech development and to study its impact on senior preschool children with autistic disorders. Prospects for further research are to study the effectiveness of digitalization in senior preschool children depending on the level of the autism spectrum.
Keywords: children; specialized mobile applications; speech development